WARM LAKES IN PERMAFROST - Fomichev,A. S. (1969)
Over many decades, researchers working in the Yakut region have often noted the unusual thermal regime of the saline Lake Moksogolookh, formed by an old channel of the Kempendyay river. What causes the unusual thermal regime of the lake. Measurements at various depths have indicated that at the surface, the water has a temperature of +13C at a depth of 0.5 meters the temperatures rises to +20C, and at 1.3 meters, it reaches +32C. Water samples taken simultaneously at these depths showed an unequal distribution of ions, in both quantity and quality. (Author) Trans. of Priroda (USSR) n4 p67 1969, by Bruce Ward.